2016
DOI: 10.1024/0301-1526/a000565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of central blood pressure - a critical review

Abstract: Summary: Vital organs are exposed to the central rather than the brachial blood pressure. To date, central blood pressure can be assessed noninvasively through the use of several devices. In this review, we critically discuss the clinical relevance of central blood pressure assessment. Considerable evidence suggests that central blood pressure is a better predictor of end-organ damage than brachial blood pressure. However, there is still uncertainty concerning the value of central pressure for predicting cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It has been shown in non-critically ill patients that the greater the ratio between systolic central and peripheral pressure, the poorer the outcome. Moreover, several factors have been reported to be associated with increased ratios, including comorbid diabetes, hypertension and cardiovascular disease [9, 2629], although conflicting results exist [30]. In our sample of stable patients, we could not determine whether the bias was related to the severity of the patients’ acute condition, to an underlying chronic vascular disease or to a combination of both.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown in non-critically ill patients that the greater the ratio between systolic central and peripheral pressure, the poorer the outcome. Moreover, several factors have been reported to be associated with increased ratios, including comorbid diabetes, hypertension and cardiovascular disease [9, 2629], although conflicting results exist [30]. In our sample of stable patients, we could not determine whether the bias was related to the severity of the patients’ acute condition, to an underlying chronic vascular disease or to a combination of both.…”
Section: Discussionmentioning
confidence: 88%
“…In a small (n = 30) randomized, double-blind, placebo-controlled trial, ACEI attained a significant decrease in central SBP than BB (average decrease of 5.2 mmHg, p < 0.0001) compared to brachial BP 29 . Moreover, the earlier small studies, meta-analysis, and a recent Japanese cross-sectional study have demonstrated that the vasodilatory antihypertensives (CCB, ARB, ACEI, alpha-blockers) lower CBP more than any non-vasodilatory class (diuretics and BB), but the brachial BP was lowered to the same level 30, 31. In the CAFE trial, conducted in 2199 patients with hypertension and receiving anti-hypertensive drugs (beta-blocker + LCD, CCB + ACEI) for 4 years in a controlled manner, despite similar brachial SBP between treatment groups (difference, 0.7 mmHg), there was substantial reduction in central SBP with ACEI + DHP-CCB versus beta-blocker + LCD (difference, 4.3 mmHg, p < 0.0001) 32 .…”
Section: Discussionmentioning
confidence: 95%